2023
DOI: 10.1097/tp.0000000000004516
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to COVID-19 mRNA Vaccination in Previous Nonresponder Kidney Transplant Recipients After Short-term Withdrawal of Mycophenolic Acid 1 and 3 Months After an Additional Vaccine Dose

Abstract: Background. The impaired immune response to coronavirus disease 2019 (COVID-19) vaccination in kidney transplant recipients (KTRs) leads to an urgent need for adapted immunization strategies. Methods. Sixty-nine KTRs without seroconversion after ≥3 COVID-19 vaccinations were enrolled, and humoral response was determined after an additional full-dose mRNA-1273 vaccination by measuring severe acute respiratory syndrome coronavirus 2–specific antibodies and neutralizing antibody activity against the Delta and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
1
15
0
1
Order By: Relevance
“…In this study, 10 KTRs showed a SARS-CoV-2 breakthrough infection with a predominantly mild course of COVID-19, which is in line with others reporting of predominantly mild courses of COVID-19 in three-times vaccinated healthy subjects (11,42,73,74) and KTRs (54,61). Interestingly, we observed evenly distributed cases of breakthrough infections in hoVac compared to heVac KTRs and KTRs with a breakthrough infection had significantly lower spike S1-specific T-cell responses as compared to uninfected KTRs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, 10 KTRs showed a SARS-CoV-2 breakthrough infection with a predominantly mild course of COVID-19, which is in line with others reporting of predominantly mild courses of COVID-19 in three-times vaccinated healthy subjects (11,42,73,74) and KTRs (54,61). Interestingly, we observed evenly distributed cases of breakthrough infections in hoVac compared to heVac KTRs and KTRs with a breakthrough infection had significantly lower spike S1-specific T-cell responses as compared to uninfected KTRs.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies that explored cellular SARS-CoV-2-specific immunity in KTRs mainly focused on assays predominantly analyzing IFN-g-related immune responses (17,18,61). This approach might lead to an underestimation of the SARS-CoV-2specific T-cell immunity in KTRs, when, e.g., IL-2-related immune responses are not detected (62).…”
Section: Discussionmentioning
confidence: 99%
“…Results on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–specific humoral response as well as safety data regarding development of donor-specific antibodies (DSAs) and changes in donor-derived cell-free DNA (dd-cfDNA) in patients with MPA withdrawal were published previously. 12,13 This additional, post hoc analysis focuses on changes in TTV load in long-term KTRs with short-term changes in immunosuppressive therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Our result matches those of other investigations that showed waning humoral immunity in KTRs after vaccination. 33–35 Therefore, the recommendation for booster vaccine doses for KTRs is of high importance, 36–38 especially since vaccination is associated with decreased risk of SARS-CoV-2 infection in KTRs. 39 …”
Section: Discussionmentioning
confidence: 99%